New Insights on the Role of Sodium in the Physiological Regulation of Blood Pressure and Development of Hypertension - Polychronopoulou, Erietta; Braconnier, Philippe; Burnier, Michel (Frontiers in Cardiovascular Medicine, 2019)
A precise maintenance of sodium and fluid balance represents an essential step in the regulation of blood pressure and alterations of this balance may lead to the development of hypertension. In recent years, several new advances have been made in our understanding of the interaction between sodium and blood pressure regulation. The first is the discovery that sodium can be stored non-osmotically in tissues like the skin and the muscle when subjects are on a high sodium diet or have a reduced renal capacity to excrete sodium. This observation has induced a change in the original model of regulation of sodium balance from a 2- to a 3-compartments model including tissue sodium accumulation and the elimination of the sodium through the skin. This finding has been made possible with the development of new technologies such as 23Na-MRI. In this new model, the immune system plays a role, thereby supporting many previous studies indicating that the immune system is a crucial co-contributor to the development of hypertension through pro-hypertensive effects in the kidney, vasculature, and brain. At last, there is now evidence that sodium can affect the gut microbiome, and induce pro-inflammatory and immune responses, which might contribute to the development of salt-sensitive hypertension.